FACS single cell index sorting is highly reliable and determines immune phenotypes of clonally expanded T cells. Issue 7 (3rd April 2018) - Penter, Livius; Dietze, Kerstin; Bullinger, Lars; Westermann, Jörg; Rahn, Hans‐Peter; Hansmann, Leo
Abstract : FACS index sorting allows the isolation of single cells with retrospective identification of each single cell's high‐dimensional immune phenotype. We experimentally determine the error rate of index sorting and combine the technology with T cell receptor sequencing to identify clonal T cell expansion in aplastic anemia bone marrow as an example.